Photosensitive luminescent polymer and its synthesis method and application

CN118027357BActive Publication Date: 2026-10-27HEBEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410178532.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-09
Publication Date
2026-10-27
Estimated Expiration
2044-02-09

AI Technical Summary

Technical Problem

[0003]但是,由于上述材料的单一发光中心,螺吡喃自由度受限,进而导致了荧光颜色单一,响应速度慢的的缺点

Benefits of technology

[0045]本发明具有双发射中心,即镧系-配合物和开环状态的螺吡喃组分,且通过调节配体以及镧系元素的种类,可以实现荧光颜色的复杂变化,同时具有自修复性能的高分子基质赋予材料快速的室温自修复功能,这是在目前的报道中所没有的。在此材料中,螺吡喃由于其自由度的充分保留,响应迅速,可在光刺激15s内,实现快速的光刺激响应能力。由于镧系配合物的存在,在紫外灯下,还具有镧系离子对应的特征光;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118027357B_ABST
    Figure CN118027357B_ABST
Patent Text Reader

Abstract

The application discloses a photosensitive fluorescent polymer and a synthesis method and application thereof. The method integrates a spiropyran component and a lanthanide complex into a polymer with self-repairing performance in a form of covalent bond, realizes a photosensitive fluorescent polymer material with double emission centers and room temperature self-repairing performance, and through simple room temperature polymerization reaction and coordination reaction, different concentrations of spiropyran derivatives and different lanthanide complex are grafted into different polymer chains, so that polymer materials capable of responding to ultraviolet light and visible light are prepared, and instantaneous color change and fluorescence color change can be recognized by naked eyes. The application has the characteristics of small dosage, room temperature self-repairing, rapid response, variable fluorescence color and the like, and can be widely used in light writing fields or information encryption and anti-counterfeiting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the preparation of a light-controlled luminescent material, and more particularly to a method for preparing a polymer material that responds rapidly to ultraviolet and visible light. Background Technology

[0002] Photosensitive luminescent polymer materials have broad application prospects in information storage, anti-counterfeiting encryption, and optical detection. In particular, spiropyran-based photosensitive materials have attracted widespread attention from researchers and have been extensively reported. For example, Yang Yuhui et al. reported a photochromic material based on tetraphenylethylene derivatives and spiropyran derivatives, achieving a fluorescence color change from blue-cyan to red (Application Publication No. CN 116655723 A); Ma Xiang et al. reported a spiropyran-based polymer material, obtained by dissolving the host material and the research material in an organic solvent, followed by solvent removal, to obtain a photochromic polymer material (Authorization Announcement No. CN 112939998 B).

[0003] However, due to the single luminescent center of the aforementioned materials, the degree of freedom of spiropyran is limited, resulting in drawbacks such as a single fluorescence color and slow response speed. Therefore, it is particularly important to develop smart materials with tunable emission color, fast response speed, and the ability to integrate multiple additional properties. Summary of the Invention

[0004] The purpose of this invention is to prepare a novel photosensitive polymer material. This invention provides a technique for preparing a photosensitive fluorescent polymer based on spiropyran derivatives, lanthanide complexes, and self-healing polymer chains. This invention covalently integrates the spiropyran component and the lanthanide complex into a self-healing polymer, achieving a photosensitive fluorescent polymer material with dual emission centers and room-temperature self-healing properties. In the preparation process, through simple room-temperature polymerization and coordination reactions, different concentrations of spiropyran derivatives and different lanthanide complexes are grafted onto different polymer chains, preparing a polymer material that rapidly responds to ultraviolet and visible light, instantly producing color and fluorescence changes visible to the naked eye. The polymer of this invention can be coated onto the surfaces of media such as metals, paper, and glass to form a photosensitive coating. This coating has the characteristics of low dosage, room-temperature self-healing, rapid response, and varied fluorescence colors, and has broad application prospects in the future.

[0005] The technical solution of this invention is as follows:

[0006] A photosensitive luminescent polymer, the polymer having the following structural formula:

[0007]

[0008] Where n = 5 to 9, m = 37 to 43;

[0009] or,

[0010]

[0011] Where y = 18–21, x = 13–15;

[0012] R1 is a complex of amino-terpyridine, hydroxy-dipyridine, or amino-o-phenanthroline with a lanthanide ion, and its structural formula is:

[0013]

[0014] Wherein, Ln is a lanthanide ion, preferably Eu. 3+ or Tb 3+ .

[0015] The method for preparing the photosensitive luminescent polymer is one of the following two methods:

[0016] Method 1 includes the following steps:

[0017] Bis(3-aminopropyl)-terminated polydimethylsiloxane (PDMS) and isophorone diisocyanate (IPDI) were dissolved in dichloromethane (DCM) to obtain a prepolymer; then, a ligand, hydroxyspiropyran, and an ethanol solution (LnCl3) of lanthanide chloride were added to the above solution, and after stirring, the target photosensitive luminescent polymer was obtained.

[0018] Add 0.33 mmol of bis(3-aminopropyl)-terminated polydimethylsiloxane (PDMS) (molecular weight 3000) to every 5 mL of dichloromethane; the molar ratio of bis(3-aminopropyl)-terminated polydimethylsiloxane (PDMS) to isophorone diisocyanate (IPDI) is 3.3:4; hydroxyspiropyran is 0.1–5‰ of the raw material mass; ligand is 0.1–25‰ of the raw material mass; Ln 3+ The molar ratio of Ln to amino-terpyridine ligand is 1:2. 3+ The molar ratio of the raw material to the pyridine or aminophenanthroline ligand is 1:3; the mass of the raw material is the sum of the masses of PDMS, IPDI and the ligand.

[0019] The structural formula of the polymer is:

[0020]

[0021] Where n = 5 to 9, m = 37 to 43.

[0022] Alternatively, method two includes the following steps:

[0023] Polytetramethylene ether glycol (PTEG) and dicyclohexylmethylmethane-4,4'-diisocyanate (HMDI) were dissolved in N,N-dimethylformamide (DMF) to obtain a prepolymer; then, a ligand, hydroxyspiropyran, and an ethanol solution (LnCl3) of lanthanide chloride were added to the above solution, and after stirring, a photosensitive luminescent polymer was prepared.

[0024] In this formulation, 1 mmol of PTEG (molecular weight 1000) is added to every 5 mL of DMF; the molar ratio of PTEG to HMDI is 1:1.3; the hydroxyspiropyran content is 0.5–10‰ of the raw material mass; the ligand content is 0.5–30‰ of the raw material mass; and Ln... 3+ The molar ratio of Ln to amino-terpyridine ligand is 1:2. 3+ The molar ratio of the raw material to the pyridine or aminophenanthroline ligand is 1:3; the mass of the raw material is the sum of the masses of PTEG, HMDI and the ligand.

[0025] The ligands in Method 1 and Method 2 may be the same or different, and may be aminotripyridine, hydroxydipyridine, or amino-o-phenanthroline;

[0026] For either method one or method two, the reaction temperature for obtaining the prepolymer is 40–80°C.

[0027] The structural formula of the polymer is:

[0028]

[0029] Where y = 18 to 21, x = 13 to 15.

[0030] In the two photosensitive luminescent polymers mentioned above, R1 is a complex of amino-terpyridine, hydroxy-dipyridine, or amino-phenanthroline with a lanthanide ion, and its structure is shown in the figure below:

[0031]

[0032] Wherein, Ln is a lanthanide ion, preferably Eu. 3+ or Tb 3+ .

[0033] The aforementioned photosensitive luminescent polymer is used in the field of optical writing or information encryption and anti-counterfeiting.

[0034] The aforementioned method for applying optical writing includes the following steps:

[0035] After drying the above-mentioned photosensitive luminescent polymer, it is cut into films of the required size, or directly coated onto the surface of substrates such as quartz plates, glass plates, and metals to form a uniform photosensitive film coating. Then, the required information is irradiated with a 365nm ultraviolet lamp for 10-30 seconds by screen printing to achieve the purpose of light writing. The ultraviolet lamp is AUX-AS-008, 15W.

[0036] The information anti-counterfeiting application method is one of the following three methods:

[0037] Method 1 includes the following steps:

[0038] When a photosensitive luminescent polymer is coated onto the surface of the substrate on which information needs to be recorded, the information written is colorless and unreadable in its original state because the photosensitive material is colorless and transparent. However, after being irradiated with a 365nm ultraviolet lamp for 10 to 30 seconds, due to the ring-opening effect of spiropyran in the material, the substrate coated with the photosensitive luminescent polymer will display the corresponding purple information.

[0039] Alternatively, method two includes the following steps:

[0040] A photoluminescent polymer is coated onto the surface of the substrate on which information needs to be recorded. In its original state, since the photosensitive material is colorless and transparent, the written information is colorless and unreadable. After being irradiated with a 365nm ultraviolet lamp for 10-30 seconds, due to the ring-opening effect of spiropyran in the material, the substrate coated with the photoluminescent polymer will display the corresponding purple information. With continued irradiation with a 365nm ultraviolet lamp, the substrate coated with the photoluminescent polymer will display red fluorescence.

[0041] Alternatively, method three includes the following steps:

[0042] A photosensitive luminescent polymer is coated onto the surface of the substrate on which information needs to be recorded. In its original state, since the photosensitive material is colorless and transparent, the written information is colorless and unreadable. After irradiation with a 365nm ultraviolet lamp for 10-30 seconds, and then irradiation with a 365nm or 302nm ultraviolet lamp, as the content of aminoterpyridine increases from 0.5mg to 8mg, the photosensitive luminescent polymer coated on the substrate changes sequentially from colorless to red emission, weak green emission to red emission, green emission to yellow emission, and then remains green emission.

[0043] The substrate is paper, glass plate or quartz sheet.

[0044] The essential features of this invention are:

[0045] This invention features dual emission centers: a lanthanide complex and an open-ring spiropyran component. By adjusting the ligands and the type of lanthanide elements, complex changes in fluorescence color can be achieved. Furthermore, the self-healing polymer matrix endows the material with rapid room-temperature self-healing capabilities, a feature not previously reported. In this material, the spiropyran, due to its fully preserved degrees of freedom, exhibits rapid response, achieving a fast photostimulation response within 15 seconds. Due to the presence of the lanthanide complex, it also displays characteristic light corresponding to lanthanide ions under ultraviolet light.

[0046] The beneficial effects of this invention are:

[0047] (1) The present invention uses spiropyran, which has good photosensitive properties, as a photosensitive dopant. While maintaining the photosensitive activity of spiropyran, it is covalently branched onto the polymer chain to give the polymer material a rapid photosensitive color-changing ability.

[0048] (2) A polymer material that emits characteristic light of corresponding lanthanide ions under strong ultraviolet light is provided. The material has certain mechanical properties and can withstand certain tensile strength and strain.

[0049] (3) The dynamic bonds in the material provide it with a rapid self-healing function at room temperature. After self-healing for 24 hours at room temperature, the tensile curve of the self-healed sample is basically consistent with the original curve, achieving a self-healing efficiency of 100%. Here, the self-healing efficiency is defined as the ratio of the toughness after self-healing to the initial toughness.

[0050] (4) The photosensitive properties of this material are visually identifiable. After being irradiated with ultraviolet light, it rapidly changes from transparent and colorless to a distinct purple under fluorescent light. Simultaneously, under a 302nm ultraviolet lamp, the material exhibits various fluorescence color changes (see reference). Figure 4The material exhibits a rapid photosensitive transition from a distinct blue light to a bright red emission at 365 nm, which can be restored to its original state using visible light. Compared to currently reported spiropyran-based materials, our material demonstrates significantly faster photosensitivity (rapid color development / fading within 15 seconds). Due to the presence of lanthanide complexes, it also exhibits characteristic light corresponding to lanthanide ions under ultraviolet light. This material possesses dual emission centers: a lanthanide complex and an open-ring spiropyran component. By adjusting the ligands and the type of lanthanide elements, complex changes in fluorescence color can be achieved. Furthermore, the self-healing polymer matrix endows the material with rapid room-temperature self-healing capabilities. This design concept, combining spiropyran with lanthanide complexes and endowing the material with self-healing abilities, is unprecedented in current reports. In addition, our material is prepared under mild conditions at room temperature; the amount of spiropyran used is low (<5‰), resulting in low cost; and due to the presence of the polymer matrix, this photosensitive polymer material exhibits excellent processing properties, allowing it to be processed into polymer films of arbitrary shapes or coated onto surfaces of metals, paper, glass, and other media to form photosensitive coatings. In summary, this photosensitive polymer material has broad application prospects in the future. Its fluorescent color and the variability in its own color control endow the material with wide application potential in information storage, encryption and anti-counterfeiting, and photowriting. For example, we can use ultraviolet light as a "pen" and screen printing technology to easily write "HEBUT" on a sample film through a writing-erasing-rewriting process. By making our samples into information dots and combining them with Morse code technology, we can prepare high-end anti-counterfeiting materials. Attached Figure Description

[0051] Figure 1 These are photographs of the photosensitive polymers obtained in Examples 1-5, showing their actual stimulus responses.

[0052] Figure 2 This is a mechanism diagram of the photosensitivity of the spiropyran component in the photosensitive polymers obtained in Examples 1-5.

[0053] Figure 3 The images show the infrared spectra of the raw materials, intermediate products, and final target product in Example 1.

[0054] Figure 4 The image shows the ultraviolet absorption spectrum of the photosensitive polymer obtained in Example 1.

[0055] Figure 5 These are real-life photos of the emission colors of the photosensitive polymers with different Tpy ratios obtained in Examples 1-5 under ultraviolet light.

[0056] Figure 6 The images show the fluorescence chromatograms of the photosensitive polymers with different Tpy ratios obtained in Examples 1-5 after ultraviolet irradiation.

[0057] Figure 7 The CIE coordinates are the emission spectra of the photosensitive polymers with different Tpy ratios obtained in Examples 1-5 after UV light treatment.

[0058] Figure 8 The image shows the UV absorption spectrum of the photosensitive polymer obtained in Example 1 after alternating UV / Vis light irradiation.

[0059] Figure 9 This is a photograph of the repeatable light writing function of the photosensitive material obtained in Example 4.

[0060] Figure 10 This illustrates the application of the photosensitive polymer obtained in Example 5 in anti-counterfeiting ink.

[0061] Figure 11 This describes the combination of the photosensitive polymer obtained in Example 1 with Morse code and its application in advanced anti-counterfeiting.

[0062] Figure 12 The image shows the actual photo-response of the photosensitive polymer obtained in Example 6.

[0063] Figure 13 This is a photograph of the photosensitive polymer stimulus response obtained in Example 7.

[0064] Figure 14 This is a photograph of the photosensitive polymer stimulus response obtained in Example 8. Detailed Implementation

[0065] To illustrate the invention more clearly, the following embodiments are provided, but they do not limit the scope of the invention in any way.

[0066] The bis(3-aminopropyl)-terminated polydimethylsiloxane (PDMS, relative molecular mass approximately 3000) involved in this invention is manufactured by Gelst Laboratories, USA, and is a viscous, transparent liquid. It is readily soluble in organic solvents such as chloroform, dichloromethane, and tetrahydrofuran, but insoluble in water. Isophorone diisocyanate (IPDI) was purchased from Shanghai Aladdin Reagent Co., Ltd.

[0067] The amino-terpyridines involved in the reaction are synthesized by, but are not limited to, the following methods:

[0068] 5-Aminopentane-1-pentanol (770 mg, 7.47 mmol) was added to a suspension containing KOH (2.00 g, 35.6 mmol) and dry DMSO (30 mL), and the mixture was stirred at 60 °C for 30 min. Subsequently, 4′-chloro-2,2′:6′,2′-bipyridine (2 g, 7.47 mol) was added to the mixture, and the mixture was stirred at 60 °C for 48 h. The mixture was then cooled and poured into 1000 mL of deionized water. The solution was then centrifuged and washed until pH 7. Finally, the product was dried in a vacuum oven at 60 °C for 3 days to obtain a yellow solid powder (2 g, 83.3%). 1 ¹H NMR (500MHz, CDCl₃) δ 8.68(s, 2H), 8.59(s, 2H), 7.99(s, 2H), 7.83(s, 2H), 7.32(s, 2H), 4.22(s, 2H), 2.73(s, 2H), 1.86(s, 2H), 1.53(s, 4H), 1.38(s, 2H). The target structural formula is:

[0069]

[0070] Other reagents can be purchased from Shanghai Aladdin Reagent Company or Shanghai McLean Reagent Company.

[0071] All solvents used are of analytical grade and can be purchased from Tianjin Fengchuan Chemicals Co., Ltd. or Tianjin Kaimate Chemicals Co., Ltd.

[0072] Example 1

[0073] (1) Dissolve 1 g (0.33 mmol) of bis(3-aminopropyl)-terminated polydimethylsiloxane in 5 mL of DCM solvent. Under magnetic stirring, add 88 mg (0.4 mmol) of IPDI reagent and continue stirring at room temperature for 3 h to obtain the prepolymer. Then add 4 mg (0.012 mmol) of aminoterpyridine and 0.5 mg (1.42 × 10⁻⁶) of hydroxyspiropyran. -3 After stirring at room temperature for 6 hours, terbium chloride hexahydrate (0.006 mmol) and excess methanol (MeOH) 1 mL were added to quench the reaction and eliminate excess -N=C=O groups. After continuing the reaction at room temperature for 0.5 hours, the resulting product solution was coated onto the desired substrate or poured into a polytetrafluoroethylene mold. After evaporation at room temperature for 24 hours and drying in a 50°C oven for 72 hours, the desired photosensitive product film with a thickness of approximately 0.2 mm was obtained. The bis(3-aminopropyl)-terminated polydimethylsiloxane (PDMS) has a molecular weight of 3000; the terbium chloride hexahydrate (TbCl3·6H2O) used is its corresponding ethanol solution with a concentration of 0.1 mol / L.

[0074] The structural formula of the polymer is shown in the figure below (labeled P4). The relative molecular masses of the polymer are approximately: Mn = 24000 g / mol, Mw = 46000 g / mol. This structure will be confirmed by its corresponding infrared spectrum in the following discussion. Figure 3 ):

[0075]

[0076] n = 8, m = 40.

[0077] Examples 2-5

[0078] The other steps are the same as in Example 1, except that the amount of aminoterpyridine feed is adjusted. The amount of aminoterpyridine is changed from 4 mg to 0.5, 1, 2, or 8 mg, respectively, to obtain a series of photosensitive polymer materials, labeled P0.5 (Example 2), P1 (Example 3), P2 (Example 4), and P8 (Example 5). Furthermore, the aminoterpyridine ligand and Tb... 3+ The molar ratio remains at 2:1.

[0079] Figure 1 The images shown are actual photographs of the photosensitive polymer films prepared in Examples 1-5. The samples were initially transparent and colorless polyurethane films. After 15 seconds of irradiation with 365nm ultraviolet light, the samples rapidly changed from colorless to deep purple. After 15 seconds of irradiation with visible light, the samples underwent the opposite change, quickly returning to their initial transparent and colorless state, confirming the material's rapid photosensitivity.

[0080] Figure 2 This is a mechanism diagram of the photosensitivity of the samples obtained in Examples 1-5. Under ultraviolet light irradiation, the spiropyran component in the polymer film can rapidly change from a colorless, ring-closed state to a deep purple, ring-open state. Under visible light irradiation, the reverse process occurs, allowing the sample to quickly return to its original state.

[0081] Figure 3 The infrared spectra of the raw materials, intermediate products, and final target product P4 in Example 1 are shown below. Curve 1 represents the raw material IPDI; curve 2 represents intermediate product A after the reaction of aminoPDMS and IPDI; curve 3 represents product B after the reaction of intermediate product A and Tpy; curve 4 represents product C after the reaction of product B and spiropyran; and curve 5 represents the representative sample of the final product, photoPU-Tb. The corresponding infrared spectra demonstrate the successful preparation of the intermediate products and the final material photoPU-Tb.

[0082] like Figure 3As shown: i) Isocyanate-terminated prepolymer A was synthesized via the polymerization reaction of IPDI and aminoPDMS. Compared with the FT-IR spectrum of the raw material IPDI, the corresponding FT-IR spectrum of prepolymer A is at 2267 cm⁻¹. -1 A weakened N=C=O peak was observed at this point, indicating that the N=C=O portion of IPDI had been converted into a urea bond. ii) Then, the intermediate A obtained in step 1 was reacted with the ligand aminoterpyridine to synthesize intermediate B. At this point, 2267 cm⁻¹... -1 The weakening peak at N=C=O further decreased. iii) Similarly, after adding hydroxyspiropyran to the system, the peak at 2267 cm⁻¹ decreased further. -1 The absorption peak at N=C=O decreased again, indicating that the hydroxyspiropyran had been successfully attached to the polymer chain. iv) Finally, an appropriate amount of LnCl3·6H2O ethanol solution and excess methanol (MeOH) were introduced into the above system. Subsequently, due to the quenching effect of MeOH, the absorption peak at 2262 cm⁻¹ decreased. -1 The weakened N=C=O peak completely disappeared, thus eliminating the residual isocyanate and proving the successful synthesis of the target product P4.

[0083] Figure 4 The image shows the ultraviolet absorption spectra of the sample in Example 1 before and after color change. The ultraviolet absorption spectra show that, in the initial state, the material exhibits virtually no absorption in the visible light range (400–800 nm), confirming its transparent and colorless properties. After 15 seconds of ultraviolet irradiation, a significant absorption peak appears at 578 nm, which is the source of the material's deep ultraviolet light, indicating that the material absorbed complementary violet light. After irradiating the discolored material with visible light for 15 seconds, the absorption peak at 578 nm disappears, and the material returns to its original transparent and colorless state.

[0084] Figure 5 These are actual photographs of the fluorescence images of the samples obtained in Examples 1-5. The feed amount of spiropyran was fixed at 0.5 mg, and the feed amount of aminopyridine (Tpy) was adjusted to 0.5, 1, 2, 4, or 8 mg, respectively, to prepare a series of variable photosensitizing materials (Note: Tpy and Tb...). 3+ The molar ratio is always 2:1. With the increase of Tpy-Tb, a variety of color changes were obtained under a 302nm UV lamp, including no emission to red emission (Tpy: 0.5, 1mg), weak green emission to red emission (Tpy: 2mg), green emission to yellow emission (Tpy: 4mg), and green emission maintained (Tpy: 8mg). At the same time, obvious red fluorescence was produced at 365nm.

[0085] Figure 6 and Figure 7The following are fluorescence emission patterns (excitation wavelength 300 nm) and their corresponding CIE coordinates of a series of samples obtained in Examples 1-5. Because the spiropyran component in the material has a sufficiently large degree of freedom during testing on the Edinburgh Instruments FS920P spectrometer, the spiropyran has transitioned from a closed-ring state (SP) to an open-ring state (MC) and emits corresponding red light. Therefore, we cannot obtain the fluorescence spectrum of the sample in its initial state, but only a series of fluorescence curves after exposure to ultraviolet radiation. Taking a 4 mg Tpy sample as an example, its emission spectrum excited at 300 nm shows emission peaks centered at 490, 542, 583, and 622 nm, which belong to... 5 D4→ 7 F J (J = 6, 5, 4, 3) transitions, where 5 D4→ 7 The peak at 542 nm generated by F5 dominated the green emission of the sample. As the Tpy content was adjusted from 0.5 mg to 8 mg (P2 to P6), the emission spectrum of the sample excited at 300 nm exhibited Tb at 542 nm. 3+ The characteristic peaks increase, and the emission color gradually changes from red to yellow to green, which is consistent with... Figure 4 Real photos and Figure 6 The emission colors in the CIE 1931 diagram are consistent.

[0086] Figure 8 For the fatigue resistance test of the product obtained in Example 1, by alternating irradiation with ultraviolet / visible light and measuring its ultraviolet absorption spectrum at room temperature, it was observed that its stimulus response remained unchanged even after 10 cycles of visible / ultraviolet light stimulation. This demonstrates that the material has good fatigue resistance.

[0087] Figure 9 This is a schematic diagram of the photowriting process of the product obtained in Example 4. Using 365nm ultraviolet light as a "pen" and visible light as an "eraser", "HEBUT" can be obtained on a single sample film through a process of writing-erasing-rewriting by screen printing.

[0088] Figure 10 This demonstrates the application of the product obtained in Example 5 in anti-counterfeiting ink. Our sample can be used to write the information "H" on A4 paper with a brush. Initially, the information is transparent and colorless. After irradiation with 365nm ultraviolet light, under fluorescent light, the letter "H" changes from transparent and colorless to deep ultraviolet. Simultaneously, green and red versions of the letter "H" are observed at 302nm and 365nm respectively. This irradiation demonstrates the application of our representative material in anti-counterfeiting ink.

[0089] Figure 11is a schematic diagram of the application of the product obtained in Example 1 in advanced anti-counterfeiting. We apply the material to a circular quartz plate to prepare an information dot matrix. Considering the fluorescence emission output performance of the material under ultraviolet light, information can be encrypted and transmitted by combining Morse code with the photostimulation response capability of our sample, where a single sample and three consecutive sample dots represent a "dot" and a "dash" respectively. As shown in Figure 9 , in the initial state, we only obtain a transparent sample array, and there is no available information at first under daylight. Subsequently, after exposure to 365 nm ultraviolet light for only 15 s, the information "LOVE" can be easily detected under daylight by decrypting the Morse code. However, the information "LOVE" is set as false information. The correct information "ARMY" can only be obtained under 302 nm ultraviolet light, while the wrong information "LOVE" can also be obtained under 365 nm ultraviolet light. The sample information array can be restored to its original state again after 15 s of exposure under visible light.

[0090] Examples 6-7

[0091] The preparation steps of the photopolymers containing the other two ligands are the same as those in Example 1, with the difference that the ligand is changed from aminoterpyridine to hydroxydipyridine or aminophenanthroline;

[0092] as shown in Figure 12 and Figure 13 , two similar photopolymer materials are obtained, which produce an obvious purple color visible to the naked eye under a fluorescent lamp after being irradiated with a 365 nm ultraviolet lamp for 15 s.

[0093] Example 8

[0094] 1 g (1 mmol) of PTEG is fully dissolved in 5 mL of DMF solvent, under magnetic stirring, 340 mg (1.3 mmol) of HMDI reagent is added, stirring is continued at 70°C for 3 h to obtain a prepolymer, then 10 mg (0.030 mmol) of aminoterpyridine and 2 mg (5.68×10 -3After stirring at room temperature for 6 hours, terbium chloride hexahydrate (0.015 mmol) or europium chloride hexahydrate (0.015 mmol) and excess methanol (MeOH) 1 mL were added to quench the reaction and eliminate excess -N=C=O groups. After continuing the reaction at room temperature for 0.5 hours, the resulting product solution was coated onto the desired substrate or poured into a polytetrafluoroethylene mold. After evaporation at room temperature for 24 hours and drying in an oven at 80°C for 72 hours, the desired photosensitive product film with a thickness of approximately 0.2 mm was obtained. The molecular weight of the PTEG was 1000; the terbium chloride hexahydrate (TbCl3·6H2O) or europium chloride hexahydrate (EuCl3·6H2O) used was their corresponding ethanol solution with a concentration of 0.1 mol / L.

[0095] Examples 9-10

[0096] The preparation steps of the photosensitive polymer containing the other two ligands are the same as in Example 8, except that the ligands are changed from amino-terpyridine to hydroxy-dipyridine or amino-o-phenanthroline, and two similar photosensitive polymer materials can also be obtained.

[0097] In summary, this photosensitive polymer material exhibits excellent photostimulation response, rapidly responding to both ultraviolet and visible light, resulting in color changes visible to the naked eye under visible light and significant fluorescence under ultraviolet light. This also demonstrates the versatility and simplicity of this method for preparing the photosensitive polymer.

[0098] Matters not covered in this invention are common knowledge.

Claims

1. A method for preparing a photosensitive luminescent polymer, characterized in that, This method is one of the following two methods: Method 1 includes the following steps: Bis(3-aminopropyl)-terminated polydimethylsiloxane and isophorone diisocyanate were dissolved in dichloromethane to obtain a prepolymer; then, a ligand, hydroxyspiropyran, and an ethanol solution of LnCl3 were added to the above solution, and after stirring, the target photosensitive luminescent polymer was obtained. Add 0.33 mmol of bis(3-aminopropyl)-terminated polydimethylsiloxane to every 5 mL of dichloromethane; the molar ratio of bis(3-aminopropyl)-terminated polydimethylsiloxane to isophorone diisocyanate is 3.3:4; hydroxyspiropyran is 0.1–5‰ of the raw material mass; ligand is 0.1–25‰ of the raw material mass, Ln 3+ The molar ratio of Ln to amino-terpyridine ligand is 1:

2. 3+ The molar ratio of the raw material to the hydroxy-bispyridine or amino-o-phenanthroline ligand is 1:3; the mass of the raw material is the sum of the masses of the bis(3-aminopropyl)-terminated polydimethylsiloxane, isophorone diisocyanate and the ligand. Alternatively, method two includes the following steps: Polytetramethylene ether glycol and dicyclohexylmethane-4,4'-diisocyanate were dissolved in N,N-dimethylformamide to obtain a prepolymer; then, a ligand, hydroxyspiropyran, and an ethanol solution of LnCl3 were added to the above solution, and after stirring, a photosensitive luminescent polymer was obtained. In this formulation, 1 mmol of polytetramethylene ether glycol is added to every 5 mL of N,N-dimethylformamide; the molar ratio of polytetramethylene ether glycol to dicyclohexylmethane-4,4'-diisocyanate is 1:1.3; hydroxyspiropyran is 0.5–10‰ of the raw material mass; the ligand is 0.5–30‰ of the raw material mass; and Ln 3+ The molar ratio of Ln to amino-terpyridine ligand is 1:

2. 3+ The molar ratio of the raw material to the hydroxybipyridine or aminophenanthroline ligand is 1:3; the mass of the raw material is the sum of the masses of polytetramethylene ether glycol, dicyclohexylmethane-4,4'-diisocyanate and the ligand. The ligands in Method 1 and Method 2 may be the same or different, and may be amino-terpyridine, hydroxy-dipyridine, or amino-o-phenanthroline; the reaction temperature for obtaining the prepolymer in either Method 1 or Method 2 is 40~80℃.

2. The application of the photosensitive luminescent polymer prepared by the method described in claim 1, characterized in that, Used in the field of optical writing or for information encryption and anti-counterfeiting.

3. The application of the photosensitive luminescent polymer as described in claim 2, characterized in that the method of applying the light writing includes the following steps: After drying the above-mentioned photosensitive luminescent polymer, it is cut into a film of the required size, or directly coated onto the surface of a quartz plate, glass plate or metal to form a uniform photosensitive film coating. Then, the required information is irradiated with a 365 nm ultraviolet lamp for 10~30 s by screen printing to achieve the purpose of photowriting.

4. The application of the photosensitive luminescent polymer as described in claim 2, characterized in that the information encryption and anti-counterfeiting application method is one of the following three methods: Method 1 includes the following steps: When a photosensitive luminescent polymer is coated onto the surface of the substrate on which information needs to be recorded, the information written is colorless and unreadable in its original state because the photosensitive material is colorless and transparent. However, after being irradiated with a 365 nm ultraviolet lamp for 10 to 30 seconds, due to the ring-opening effect of spiropyran in the material, the substrate coated with the photosensitive luminescent polymer will display the corresponding purple information. Alternatively, method two includes the following steps: A photoluminescent polymer is coated onto the surface of the substrate on which information needs to be recorded. In its original state, since the photosensitive material is colorless and transparent, the written information is colorless and unreadable. After being irradiated with a 365 nm ultraviolet lamp for 10-30 seconds, due to the ring-opening effect of spiropyran in the material, the substrate coated with the photoluminescent polymer will display the corresponding purple information. With continued irradiation with a 365 nm ultraviolet lamp, the substrate coated with the photoluminescent polymer will show red fluorescence. Alternatively, method three includes the following steps: When a photosensitive luminescent polymer is coated onto the surface of a substrate on which information needs to be recorded, the information written is colorless and unreadable in its original state because the photosensitive material is colorless and transparent. After irradiation with a 365 nm UV lamp for 10-30 seconds, followed by irradiation with a 365 nm or 302 nm UV lamp, the substrate coated with the photosensitive luminescent polymer changes sequentially from colorless to red emission, weak green emission to red emission, green emission to yellow emission, and then remains green emission as the content of aminoterpyridine increases from 0.5 mg to 8 mg.

5. The application of the photosensitive luminescent polymer as described in claim 4, characterized in that, The substrate is paper, glass plate or quartz sheet.

Citation Information

Patent Citations

  • Spiropyran derivatives, photochromic materials and their preparation methods

    CN112939998B